Targeted Disruption of Ephrin B1 in Cells of Myeloid Lineage Increases Osteoclast Differentiation and Bone Resorption in Mice - Cheng, Shaohong (Public Library of Science, 2012)
Disruption of ephrin B1 in collagen I producing cells in mice results in severe skull defects and reduced bone formation. Because ephrin B1 is also expressed during osteoclast differentiation and because little is known on the role of ephrin B1 reverse signaling in bone resorption, we examined the bone phenotypes in ephrin B1 conditional knockout mice, and studied the function of ephrin B1 reverse signaling on osteoclast differentiation and resorptive activity. Targeted deletion of ephrin B1 gene in myeloid lineage cells resulted in reduced trabecular bone volume, trabecular number and trabecular thickness caused by increased TRAP positive osteoclasts and bone resorption. Histomorphometric analyses found bone formation parameters were not changed in ephrin B1 knockout mice. Treatment of wild-type precursors with clustered soluble EphB2-Fc inhibited RANKL induced formation of multinucleated osteoclasts, and bone resorption pits. The same treatment of ephrin B1 deficient precursors had little effect on osteoclast differentiation and pit formation. Similarly, activation of ephrin B1 reverse signaling by EphB2-Fc treatment led to inhibition of TRAP, cathepsin K and NFATc1 mRNA expression in osteoclasts derived from wild-type mice but not conditional knockout mice. Immunoprecipitation with NHERF1 antibody revealed ephrin B1 interacted with NHERF1 in differentiated osteoclasts. Treatment of osteoclasts with exogenous EphB2-Fc resulted in reduced phosphorylation of ezrin/radixin/moesin. We conclude that myeloid lineage produced ephrin B1 is a negative regulator of bone resorption in vivo, and that activation of ephrin B1 reverse signaling inhibits osteoclast differentiation in vitro in part via a mechanism that involves inhibition of NFATc1 expression and modulation of phosphorylation status of ezrin/radixin/moesin.